Characterization of the complete mitochondrial genome of Neoasterolepisma foreli (Insecta: Zygentoma: Lepismatidae) and the phylogeny of basal Ectognatha. Issue 1 (2nd January 2021) - Cucini, Claudio; Carapelli, Antonio; Brunetti, Claudia; Molero-Baltanás, Rafael; Gaju-Ricart, Miquel; Nardi, Francesco
Abstract: The silverfish Neoasterolepisma foreli belongs to the family Lepismatidae within Zygentoma and is well known for the peculiar habit of living in strict association with ant nests (myrmecophily). In this study, we describe its mitochondrial genome, a circular molecule of 15, 398 bp including the canonical 13 PCGs, 22 tRNAs, 2 rRNAs, as well as a 403 bp AT-rich region. A phylomitogenomic analysis of the new sequence, alongside basal hexapod mtDNAs, confirmed the monophyly of all orders, with some uncertainty over the position of the enigmatic Tricholepidion gertschi that would make Zygentoma paraphyletic. Neoasterolepisma foreli is recovered in a basal position within family Lepismatidae, at odd with our current understanding of the group that would, in turn, suggest a closer relationship with the genus Lepisma (Mendes, 1991 ).